The effects of L-carnitine supplement on anemia in hemodialysis patients: A randomized clinical trial study - Avin Khorshidi (Chronic Diseases Journal, 2021)
BACKGROUND: There is no general consensus about the effect of L-carnitine (LC) on anemic factors in hemodialysis patients. In this clinical trial, the effect of LC on anemia was investigated in these patients.